2015
DOI: 10.1161/atvbaha.114.304292
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Cathepsin C Deficiency Attenuates Atherosclerotic Lesion Progression by Selective Tuning of Innate and Adaptive Immune Responses

Abstract: Objective The protein degrading activity of Cathepsin C, combined with its role in leukocyte granule activation, suggests a contribution of this cystein protease in atherosclerosis. However, no experimental data are available to validate this concept. Approach and results CatC gene and protein expression were increased in ruptured versus advanced stable human carotid artery lesions. To assess causal involvement of CatC in plaque progression and stability, we generated LDLr−/−//CatC−/− chimeras by bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…DPPI deficiency also attenuates early atherosclerotic lesion in LDL-receptor-deficient mice (40). A recent report established that the absence of DPPI abrogates in vitro NET formation (13).…”
Section: Discussionmentioning
confidence: 99%
“…DPPI deficiency also attenuates early atherosclerotic lesion in LDL-receptor-deficient mice (40). A recent report established that the absence of DPPI abrogates in vitro NET formation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using this technique, it has been demonstrated that cathepsin C deficiency 62 , CD43 (an integral membrane glycoprotein), 63 CC chemokine ligand 3, 64 or angiotensin-converting enzyme (a critical enzyme to generate angiotensin II) 65 in leukocytes led to reductions of atherosclerosis in hypercholesterolemic mice at a single time point. In mice studied at multiple durations of Western diet feeding, deficiency of the common β subunit of the granulocyte macrophage colony-stimulating factor/interleukin-3 receptor in leukocytes only reduced lesion size transiently.…”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%
“…Also, total mitochondrial biogenesis and mitophagy did not seem to be altered significantly. However, the lysosomal degradation of immunological targets was strongly upregulated together with phagocytosis and endosomal pathways, with the strongest upregulations concerning Ctsz and Ctsc which act in innate immune pathways [69,70]. Furthermore, it seemed credible furthermore that LonP1 deficiency affects the import of mitochondrial precursor proteins, since the mitochondrial import receptor Tomm70a, the import peptidase Pmpcb and the folding chaperone Hspd1 had significantly altered abundances.…”
Section: Discussionmentioning
confidence: 99%